Occupational Health and Safety Analysis Using HIRA and FTA Methods in the Silo Department of PT. XYZ - Muhammad Maulidun Na’am; Deny Andesta; Elly Ismiyah (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
PT. XYZ is a wheat flour producer. To produce quality flour requires risky labor. Work accidents from 2014 to 2022 were evaluated based on secondary data. This research detects work accidents in the Silo Department using the Hazard Identification And Risk Analysis (HIRA) and Fault Tree Analysis (FTA) methods. HIRA is used to detect risks and causes of work accidents. There are six activities in a silo that have the potential to cause work accidents, namely: stairs without handrails, sample display areas without steps, top steps that are loose and protrude upwards, open dump truck doors, placement of elevator chains, and opening ventilation at the top of the silo. Based on the results of the FTA analysis, it is known that the causes of work accidents are caused by ladders not being suitable for use, workers not using PPE, workers not understanding the work flow, workers being tired, workers not concentrating, workers being in a hurry. PT. XYZ adalah produsen tepung terigu. Untuk memproduksi tepung yang berkualitas memerlukan tenaga kerja yang berisiko. Kecelakaan kerja dari tahun 2014 hingga 2022 dievaluasi berdasarkan data sekunder. Penelitian ini mendeteksi kecelakaan kerja di Departemen Silo dengan menggunakan metode Hazard Identification And Risk Analysis (HIRA) dan Fault Tree Analysis (FTA). HIRA digunakan untuk mendeteksi risiko dan penyebab kecelakaan kerja. Terdapat enam aktivitas dalam silo yang berpotensi menimbulkan kecelakaan kerja, yaitu : tangga tanpa pegangan, area display sampel tanpa undakan, anak tangga paling atas yang kendur dan menonjol ke atas, pintu dump truck terbuka, penggantian rantai elevator, serta pembukaan ventilasi silo bagian atas. Berdasarkan hasil analisis FTA diketahui penyebab terjadinya kecelakaa kerja dikarenakan tangga tidak layak pakai, pekerja tidak menggunakan APD, pekerja tidak memahami alur kerja, pekerja dalam kondisi lelah pekerja tidak konsentrasi, pekerja tergesah-gesah.